The Development of Technical and Vocational Education in Libya in Light of the Experiences of Some Contemporary Countries: A Comparative Study . (Al-Farooq Journal of Sciences, 2026)
This study focuses on anticipating the innovation process in Libya, where technicaland vocational education is prevalent. It does so by conducting a comparative study with the experiences of advanced technology institutions (such as Malaysia and Germany) to surpass their successful models. The research employs a comparative and descriptive-analytical approach to diagnose the current situation, particularly regarding technical curricula in Libya, based on the most prominent experiences, funding, and societal challenges facing the sector. The study arrives at a matrix of key findings, highlighting a unique phenomenon between technical colleges and institutes and the real labor market, in addition to the obsolescence of information technology and laboratories. The study begins by identifying an effective mechanism for utilizing updated legislation, fostering creative collaboration skills with oil industry innovators, and establishing a societal model for technical pathways
Keywords: Technical education, vocational education, comparative study, Libyan labor market, curriculum development